Low-temperature high-power lithium ion battery
The low-temperature high-power lithium-ion battery addresses performance issues in extreme temperatures by using modified electrodes and an optimized electrolyte, achieving high-rate discharge and extended cycle life in low-temperature conditions.
Patent Information
- Application Number
- CN202411444044.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-16
AI Technical Summary
Traditional lithium-ion batteries perform poorly in extreme temperatures below 0°C or above 40°C due to slowed lithium ion transfer, decreased ionic conductivity, anode lithium plating, lithium dendrite growth, and thickening of the solid electrolyte interface film, leading to capacity decay and cycle rate deterioration.
A low-temperature high-power lithium-ion battery design featuring a modified positive electrode with boron-doped titanium dioxide nanotube array immobilized molybdenum disulfide and a modified negative electrode with forged needle coke secondary particles coated with inorganic carbon, combined with an optimized electrolyte composition, to enhance lithium ion diffusion and conductivity.
The battery achieves high-rate discharge performance and extended cycle life in low-temperature environments, supporting discharge rates up to 20C at -20°C, 10C at -30°C, and 3C at -40°C, with improved conductivity and stability, meeting the needs of military and aerospace applications.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a low-temperature and high-power lithium-ion battery. Background Art
[0002] Low-temperature batteries can be used in polar unmanned reconnaissance aircraft, walkie-talkies, as well as electronic vaporizers and smart devices in low-temperature areas. The military and aerospace industries also urgently need the development of low-temperature lithium-ion batteries.
[0003] Traditional lithium-ion batteries can no longer meet the requirements of working in extreme temperatures. Their life and performance are greatly affected by working ambient temperatures below 0°C or above 40°C. The main reasons for the degradation of lithium-ion battery performance at low temperatures include:
[0004] (1) The mass transfer process of lithium ions inside the electrode and at the electrode / electrolyte interface slows down;
[0005] (2) The ionic conductivity of the electrolyte decreases;
[0006] (3) Anode lithium plating and lithium dendrite growth and SE I film thickening;
[0007] (4) The desolvation process of lithium ions is difficult.
[0008] At low temperatures, the slowdown of the kinetic rate of lithium ions is the most important factor affecting its electrochemical performance. Under low temperature conditions, the battery capacity decays, the cycle rate performance deteriorates, and lithium precipitation is obvious. Domestic low-temperature lithium-ion battery development is mainly focused on electronic digital products. Low temperatures are generally achieved at -20-30℃, supporting 0.2C discharge. Military products can achieve a minimum of -40℃ and support 0.1-0.2C discharge. In order to meet the market demand for low-temperature high-rate discharge lithium-ion batteries, it is urgent to develop lithium-ion battery products that adapt to low-temperature environments and have high-rate performance. Summary of the invention
[0009] In order to solve the above technical problems, the present application provides a low-temperature high-power lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet is coated with a modified positive electrode material, and the negative electrode sheet is coated with a modified negative electrode material;
[0010] The modified positive electrode material is modified by coating a composite material on the positive electrode material, and the composite material is boron-doped titanium dioxide nanotube array immobilized molybdenum disulfide;
[0011] The modified negative electrode material is prepared by designing graphite into forged needle coke secondary particles, introducing inorganic carbon on the surface of the forged needle coke secondary particles, and forming a liquid carbon coating layer after asphalt carbonization;
[0012] The electrolyte composition includes 10-15% lithium salt, 70%-80% solvent system and 10-15% additive.
[0013] Preferably, the steps of preparing the negative electrode sheet include:
[0014] S101, preparation of modified negative electrode material: mixing graphite and inorganic carbon at a certain temperature, so that the inorganic carbon is evenly coated on the surface of graphite, and then performing asphalt carbonization treatment on the coated graphite to obtain a modified negative electrode material;
[0015] S102, the modified negative electrode material, the conductive agent and the binder are mixed in a mass ratio of (93-96): (1-4): (1-3), and prepared into a slurry by a high-speed dispersing device. After coating, roller compaction and slitting, a negative electrode sheet of corresponding length is made, and a copper-plated composite nickel tab is welded to the middle position of the negative electrode sheet and glued to obtain a negative electrode sheet.
[0016] Preferably, in step S101, the preparation steps of the modified negative electrode material include:
[0017] A1. Graphite and inorganic carbon are mixed at a mass ratio of (3-4): (1-2) at a temperature of 80-90° C., so that the inorganic carbon is evenly coated on the surface of the graphite, and then the coated graphite is cured, pyrolyzed and asphalt carbonized;
[0018] A2, using chemical vapor deposition method, placing the product of step A1 in an ethylene atmosphere at a temperature of 150-200° C. for a reaction time of 1-2 hours;
[0019] A3, placing the product of step A2 in a reactor, mixing the effective components of ethylene tar and catalytic oil slurry in a ratio of (1-2): (1-2) and adding them to the reactor, adding the catalyst and the cross-linking agent to the reactor, heating to 240-330° C., controlling the reaction pressure to 0.5-2.5 MPa, the stirring speed of the reactor to 150-450 r / min, and the reaction time to 3-4 h;
[0020] A4. Slowly release the pressure to normal pressure, introduce air into the bottom of the reactor at an air intake rate of 0.5-2L / min, stir the reactor at a speed of 200-350r / min, set the reaction temperature at 240-300°C, and react for 2-6h. Stop introducing air and stirring, and then remove the light components to obtain the modified negative electrode material.
[0021] Preferably, the catalyst is p-toluenesulfonic acid, and its content is 3%-8% of the total mass of the raw materials; the cross-linking agent is one of trioxymethylene and polyoxymethylene, and its content is 7%-12% of the total mass of the raw materials.
[0022] Preferably, the conductive agent is a mixture of superconducting carbon black and SWCNT single-walled carbon tubes, and the binder is PAA polyacrylonitrile multipolymer emulsion.
[0023] Preferably, the steps of preparing the positive electrode sheet include:
[0024] S201, preparation of composite materials, electrochemically anodic boronizing a titanium sheet in an organic solution containing 0.5wt% NH4BF4, 5wt% deionized water and ethylene glycol as solvent, and then anodic oxidation in an organic solution containing fluoride ions, heat treating the oxidized sample in a resistance furnace at 200-450°C, keeping the temperature for 2h, and then cooling it to room temperature with the furnace; using the heat-treated boron-doped titanium oxide nanoarray as a matrix, vacuumizing and heating, and then sputtering a molybdenum disulfide target with a radio frequency power supply, cooling to 45°C and taking it out to obtain a composite material;
[0025] S202, mixing the composite material and the positive electrode active material at a certain temperature, so that the composite material is evenly coated on the surface of the positive electrode active material, and then curing the positive electrode active material coated with the composite material to obtain a modified positive electrode material;
[0026] S203, the modified positive electrode material, the conductive agent and the binder are mixed in a mass ratio of (96-98): (1-2): (1-2), and prepared into a slurry by a high-speed dispersing device. After coating, roller compaction and slitting, a positive electrode sheet of corresponding length is made, and a copper-plated composite nickel electrode ear is formed in the middle of the positive electrode sheet and glued.
[0027] Preferably, in step S202, the composite material and the positive electrode active material are mixed at a mass ratio of (3-4): (1-2) at a temperature of 80-90°C.
[0028] Preferably, the positive electrode active material is prepared by adding lithium cobalt oxide, ternary material and lithium manganese oxide into a stirring tank in a ratio of (1-2): (5-7): (2-3) and mixing.
[0029] Preferably, the solvent components of the electrolyte include ethyl acetate, methyl propionate and methyl acetate; the lithium salt includes lithium bis(fluorosulfonyl)imide, and the additives include vinyl sulfate and triphosphite.
[0030] Preferably, the mass ratio of ethyl acetate, methyl propionate and methyl acetate is (1-2):(1.5-2):(1-3); the mass ratio of vinyl sulfate and triphosphite is (1-2):(1-2).
[0031] From the above, it can be seen that the following beneficial effects can be obtained by applying the method provided by this application:
[0032] 1. The negative electrode material adopts the liquid phase carbon coating design of forged needle coke secondary particle graphite. A coating layer that can make Li+ diffuse quickly is introduced on the graphite surface, which not only plays a role in the rapid transmission from the surface to the inside, but also avoids the local enrichment of Li+. In addition, the coating material for the fast ion channel is strictly controlled to control the content of impurities and foreign matter, and avoid blocking the transmission channel of Li+. Improve the battery's rate and low-temperature high-rate discharge performance, enhance the battery's rapid charge and discharge capabilities, and meet the needs of high-power applications in low-temperature environments.
[0033] 2. By optimizing the electrolyte formula and additives, as well as the coating design of modified negative electrode materials, a stable solid electrolyte interface layer (SE I) film can be formed, inhibiting the unstable growth of the SE I film, extending the cycle life of the battery and improving safety.
[0034] 3. Boron-doped titanium dioxide nanotubes are used as coating materials, which can establish a fast ion channel network on the surface of the positive electrode material, accelerate the transmission rate of lithium ions inside the positive electrode material, and thus improve the high-rate discharge performance and low-temperature performance of the battery. Boron-doped titanium dioxide nanotubes have an orderly structure that can effectively transmit electrons, improve the conductivity of the positive electrode material to electrons, and help improve the rate discharge capacity and cycle stability of the battery. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0036] Example
[0037] In order to solve the above technical problems, this embodiment provides a low-temperature high-power lithium-ion battery, including a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein a modified positive electrode material is coated on the positive electrode sheet, and a modified negative electrode material is coated on the negative electrode sheet; wherein the modified positive electrode material is coated and modified on the positive electrode material using a composite material, and the composite material is a boron-doped titanium dioxide nanotube array immobilized with molybdenum disulfide to improve the conductivity and ion transfer rate of the battery. The modified negative electrode material is obtained by designing graphite into forged needle coke secondary particles, introducing inorganic carbon on the surface of the forged needle coke secondary particles, and forming a liquid carbon coating layer after asphalt carbonization; the electrolyte composition includes 10-15% lithium salt, 70%-80% solvent system and 10-15% additives. The graphite negative electrode uses forged needle coke secondary particles. This structure can reduce the aggregate particle size and shorten the diffusion distance, so that the battery has both high rate performance and low-temperature kinetic performance. Then, the innovation of the coating material improves the diffusion rate and stability of lithium ions in the negative electrode material, thereby improving the high-rate discharge performance and low-temperature performance of the battery.
[0038] Specifically, the steps of preparing the negative electrode sheet include:
[0039] S101, preparation of modified negative electrode material: mixing graphite and inorganic carbon at a certain temperature, so that the inorganic carbon is evenly coated on the surface of graphite, and then performing asphalt carbonization treatment on the coated graphite to obtain a modified negative electrode material;
[0040] Specifically, in step S101, the preparation steps of the modified negative electrode material include:
[0041] A1. Graphite of the forged needle coke secondary particles and inorganic carbon are mixed at a mass ratio of (3-4): (1-2) at a temperature of 80-90° C., so that the inorganic carbon is uniformly coated on the surface of the graphite, and then the coated graphite is cured, pyrolyzed and asphalt carbonized;
[0042] A2, using chemical vapor deposition method, placing the product of step A1 in an ethylene atmosphere at a temperature of 150-200° C. for a reaction time of 1-2 hours;
[0043] A3, placing the product of step A2 in a reactor, mixing the effective components of ethylene tar and catalytic oil slurry in a ratio of (1-2): (1-2) and adding them to the reactor, adding the catalyst and the cross-linking agent to the reactor, heating to 240-330° C., controlling the reaction pressure to 0.5-2.5 MPa, the stirring speed of the reactor to 150-450 r / min, and the reaction time to 3-4 h;
[0044] In the above scheme, the catalyst is p-toluenesulfonic acid, and its content is 3%-8% of the total mass of the raw materials; the cross-linking agent is one of trioxymethylene and polyoxymethylene, and its content is 7%-12% of the total mass of the raw materials.
[0045] A4. Slowly release the pressure to normal pressure, select 0.5-2L / min of air intake at the bottom of the reactor, 200-350r / min of stirring speed of the reactor, 240-300℃ of reaction temperature, 2-6h of reaction time, stop introducing air and stirring, and then remove the light components to obtain a liquid carbon-coated modified negative electrode material. Inorganic carbon is introduced on the surface of the secondary particles of needle coke after forging, and the liquid carbon coating formed after asphalt carbonization can effectively increase the diffusion rate of lithium ions, reduce the internal resistance of the battery, and improve the low-temperature rate discharge efficiency of the battery. This coating can also protect the negative electrode material from the erosion of the electrolyte and extend the service life of the battery.
[0046] S102, the modified negative electrode material, the conductive agent, and the binder are mixed in a mass ratio of (93-96): (1-4): (1-3), and a slurry is prepared by a high-speed dispersing device. After the substrate is coated, rolled and slit, a negative electrode sheet of corresponding length is prepared, and a copper-plated composite nickel pole ear is welded in the middle of the negative electrode sheet and glued to obtain a negative electrode sheet. By selecting the forged needle coke secondary particle carbon coating design, it is possible to ensure that the fast ion channel is unobstructed, avoid the presence of impurities and foreign matter that hinder the transmission of lithium ions, increase the Li+ transmission rate of the negative electrode material, and improve the fast charge and discharge and low temperature performance of the battery. This design can effectively improve the conductivity of the negative electrode material, thereby improving the power and low temperature discharge performance of the battery.
[0047] Among them, the substrate of the negative electrode sheet adopts a carbon-coated copper foil structure, and a copper-plated composite nickel strip is used as the pole ear, which can improve the current transmission capacity and thermal conductivity of the pole sheet, reduce the contact resistance between the pole sheet and the battery cell, and further improve the battery's power and low-temperature discharge performance.
[0048] Furthermore, the conductive agent is a mixture of superconducting carbon black and SWCNT single-walled carbon tubes, which can improve the conductivity of the negative electrode, reduce the internal resistance of the battery, and thus improve the rate performance and low-temperature performance of the battery. The binder is a PAA polyacrylonitrile multipolymer emulsion. Using PAA polyacrylonitrile multipolymer emulsion as a binder can improve the structural stability of the pole piece, improve the mechanical strength and corrosion resistance of the pole piece, reduce the impedance of the battery cell, and improve the rate and low-temperature rate performance of the battery.
[0049] Furthermore, the steps of preparing the positive electrode sheet include:
[0050] S201, preparation of composite materials, electrochemically anodic boronizing the titanium sheet in an organic solution containing 0.5wt% NH4BF4, 5wt% deionized water and ethylene glycol as solvents, and then anodic oxidation in an organic solution containing fluoride ions, heat treating the oxidized sample in a 200-450℃ resistance furnace, keeping the temperature for 2h, and then cooling to room temperature with the furnace; using the heat-treated boron-doped titanium oxide nanoarray as a matrix, vacuuming and heating, and then sputtering the molybdenum disulfide target with a radio frequency power supply, cooling to 45℃ and taking out to obtain a composite material; boron-doped titanium dioxide nanotubes have an orderly arranged structure, which can effectively transmit electrons, improve the conductivity of the positive electrode material to electrons, and help improve the rate discharge capacity and cycle stability of the battery. By applying this coated modified material to lithium-ion battery pole pieces, the overall performance of the battery can be improved in terms of power, capacity and cycle life.
[0051] S202, mixing the composite material and the positive electrode active material at a certain temperature so that the composite material is evenly coated on the surface of the positive electrode active material, and then curing the coated positive electrode active material to obtain a modified positive electrode material, wherein the positive electrode active material is lithium cobalt oxide; in this step, the composite material and the positive electrode active material are mixed at a mass ratio of (3-4): (1-2) at a temperature of 80-90°C.
[0052] S203, the modified positive electrode material, the conductive agent, and the binder are mixed in a mass ratio of (96-98): (1-2): (1-2), and a slurry is prepared by a high-speed dispersing device. The substrate is coated, rolled, and cut to form a positive electrode sheet of corresponding length, and a copper-plated composite nickel tab is formed in the middle of the positive electrode sheet and glued. The substrate of the positive electrode sheet is a carbon-coated aluminum foil, which can reduce the polarization internal resistance of the battery, increase the conductivity of the ions, and improve the rate performance and low-temperature high-power discharge performance of the battery.
[0053] By immobilizing molybdenum disulfide on boron-doped titanium dioxide nanotubes, a composite material with good electrochemical properties is formed. As a coating modification material for positive electrode materials, since boron-doped titanium dioxide nanotubes are used as coating materials, a fast ion channel network can be established on the surface of the positive electrode material, accelerating the transmission rate of lithium ions inside the positive electrode material, thereby improving the high-rate discharge performance and low-temperature performance of the battery. In addition, boron-doped titanium dioxide nanotubes have high high temperature resistance and chemical stability, can maintain the stability of the material structure during the operation of the battery, reduce the aging rate of the battery, and extend the service life of the battery. In addition, the above-mentioned positive electrode sheet modification method does not require the use of toxic or environmentally polluting solvents and additives, has high environmental friendliness and sustainability, and is in line with the development trend of green manufacturing. This is not only conducive to improving the competitiveness of products, but also can contribute to environmental protection.
[0054] In the above scheme, the positive electrode active material is prepared by mixing lithium cobalt oxide, ternary material and lithium manganese oxide in a mixing tank according to the ratio of (1-2): (5-7): (2-3). The positive electrode active material is a mixture of lithium cobalt oxide, ternary material and lithium manganese oxide. The proper raw material ratio is designed to mix and dope to improve the stability of the positive electrode under overcharge conditions, while taking into account the energy density and providing the cycle life of the battery.
[0055] The solvent components of the electrolyte include ethyl acetate, methyl propionate and methyl acetate; the lithium salt includes lithium bis(fluorosulfonyl)imide, and the additives include vinyl sulfate and triphosphite. Low-viscosity solvents such as ethyl acetate, methyl propionate and methyl acetate have good solubility and low viscosity, which help to improve the ion transfer rate of the electrolyte, reduce the internal resistance of the battery, and improve the rate discharge and low-temperature discharge performance. It can also provide a higher solubility to ensure the full dissolution of the lithium salt, increase the concentration of lithium ions in the electrolyte, and thus increase the energy density of the battery. Using lithium bis(fluorosulfonyl)imide as a high dissociation lithium salt can increase the concentration of lithium ions in the electrolyte, thereby reducing the concentration polarization impedance and improving the rate performance and low-temperature performance of the battery. Vinyl sulfate and triphosphite as electrolyte additives can form a solid electrolyte interface (SE I) film with high Li+ conductivity, inhibit the growth of harmful SE I films, thereby reducing the impedance of ions passing through the solid electrolyte and reducing the polarization loss of the battery. These additives can also form a loose and porous solid electrolyte interface between the positive and negative electrodes of the battery cell, reduce the interface resistance, and improve the power and low-temperature rate performance of the battery. Through these optimization schemes, the rate performance and low-temperature high-rate discharge performance of the battery are significantly improved, providing more reliable energy for applications in the fields of military industry, aerospace, drones, electronic atomizers, energy storage, etc.
[0056] Wherein, the mass ratio of ethyl acetate, methyl propionate and methyl acetate is (1-2):(1.5-2):(1-3); the mass ratio of vinyl sulfate and triphosphite is (1-2):(1-2). Preferably, the mass ratio of ethyl acetate, methyl propionate and methyl acetate is 1:1.5:2, and the mass ratio of vinyl sulfate and triphosphite is 1:1.
[0057] Low-temperature, high-power discharge polymer lithium-ion battery products that support rate discharge in a low-temperature environment of -20℃, the technical indicators are as follows: Capacity: 2.5Ah (9.25wh), rated voltage: 4.2V, operating temperature: -20℃-60℃, charging cut-off voltage: 4.2V, charging current: 600mA, discharge cut-off voltage: 3.0V, maximum continuous discharge current: 20C capacity retention rate > 90%, minimum discharge temperature: -20℃, low-temperature discharge performance: stored at -20℃ for 4h and discharged at 10C, the discharge capacity retention rate is > 85%.
[0058] Temperature ℃ Initial voltage V Discharge rate C Discharge current mA Discharge capacity mAh Capacity retention rate % 25 4.198 0.2 500 2558 100% -20 4.193 10.0 25000 2250 88.0%
[0059] Table 1
[0060] Table 1 is a table showing the discharge data of the low-temperature high-power lithium-ion battery of this embodiment stored at -20°C for 4 hours and at 10C.
[0061] Low-temperature, high-power discharge polymer lithium-ion battery products that support rate discharge in a low-temperature environment of -30℃. The product technical indicators are as follows: Capacity: 0.6Ah (2.22wh), rated voltage: 4.2V, operating temperature: -30℃-60℃, charging cut-off voltage: 4.2V, charging current: 600mA, discharge cut-off voltage: 3.0V, maximum continuous discharge current: 20C capacity retention rate > 90%, minimum discharge temperature: -30℃, low-temperature discharge performance: stored at -30℃ for 4h and discharged at 5C, the discharge capacity retention rate is > 90%.
[0062] Temperature ℃ Initial voltage V Discharge rate C Discharge current mA Discharge capacity mAh Capacity retention rate % 25 4.201 0.2 120 608 100% -30 4.192 5.0 3000 556 91.4%
[0063] Table 2
[0064] Table 2 is a table of discharge data of the low-temperature high-power lithium-ion battery of this embodiment stored at -30°C for 4h and 5C.
[0065] Low-temperature, high-power discharge polymer lithium-ion battery products that support rate discharge in a low-temperature environment of -30℃. The product technical indicators are as follows: Capacity: 10Ah (37wh), rated voltage: 4.2V, operating temperature: -40℃-60℃, charging cut-off voltage: 4.2V, charging current: 20A, discharge cut-off voltage: 3.0V, maximum continuous discharge: 300A, minimum discharge temperature: -40℃, low-temperature discharge performance: stored at -30℃ for 4h and discharged at 5C, the discharge capacity retention rate is >80%.
[0066] Temperature ℃ Initial voltage V Discharge rate C Discharge current mA Discharge capacity mAh Capacity retention rate % 25 4.198 0.2 2000 10128 100% -40 4.189 3.0 30000 8765 86.5%
[0067] Table 3
[0068] Table 3 is a table showing the discharge data of the low-temperature high-power lithium-ion battery of this embodiment stored at -40°C for 4h and 3C.
[0069] From the above, it can be seen that the low-temperature high-power lithium-ion battery of this embodiment is -40°C and has a relatively significant advancement. Specifically, it is manifested in the following aspects:
[0070] 1) Extreme low temperature working ability: The battery product can work normally in an extremely low temperature environment of -40℃ and has good discharge performance, which is a relatively cutting-edge and advanced technical level in the field of lithium-ion batteries.
[0071] 2) High-power discharge capability: The battery product has a high discharge power, with a maximum continuous discharge of up to 300A, which is an advanced level of high-power discharge in the field of lithium-ion batteries and can meet application scenarios with high requirements for high-power discharge.
[0072] 3) Wide temperature range operation: The operating temperature range of the battery product is from -40℃ to 60℃, which is an extremely wide temperature range that can meet the use requirements in various extreme environments and reflects the product's advanced adaptability under extreme conditions.
[0073] 4) Excellent low-temperature discharge performance: Even at a low temperature of -40°C, it can still maintain 80% of the discharge capacity when discharged at 3C, which shows that the battery product has excellent performance under extremely cold conditions and provides reliable energy support for applications in extremely cold environments.
[0074] The above-described implementation methods do not constitute a limitation on the protection scope of the technical solution. Any modification, equivalent replacement and improvement made within the spirit and principle of the above-described implementation methods shall be included in the protection scope of the technical solution.
Claims
1. A low-temperature, high-power lithium-ion battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet is coated with a modified positive electrode material, and the negative electrode sheet is coated with a modified negative electrode material; The modified positive electrode material is modified by coating a composite material on the positive electrode material, and the composite material is boron-doped titanium dioxide nanotube array immobilized molybdenum disulfide; The modified negative electrode material is prepared by designing graphite into forged needle coke secondary particles, introducing inorganic carbon on the surface of the forged needle coke secondary particles, and forming a liquid carbon coating layer after asphalt carbonization; The electrolyte composition includes 10-15% lithium salt, 70%-80% solvent system and 10-15% additive.
2. The low-temperature, high-power lithium-ion battery according to claim 1, characterized in that: The steps of preparing the negative electrode sheet include: S101, preparation of modified negative electrode material: mixing graphite and inorganic carbon at a certain temperature, so that the inorganic carbon is evenly coated on the surface of graphite, and then performing asphalt carbonization treatment on the coated graphite to obtain a modified negative electrode material; S102, the modified negative electrode material, the conductive agent and the binder are mixed in a mass ratio of (93-96): (1-4): (1-3), and prepared into a slurry by a high-speed dispersing device. After coating, roller compaction and slitting, a negative electrode sheet of corresponding length is made, and a copper-plated composite nickel tab is welded to the middle position of the negative electrode sheet and glued to obtain a negative electrode sheet.
3. The low-temperature, high-power lithium-ion battery according to claim 2, characterized in that: In step S101, the preparation steps of the modified negative electrode material include: A1. Graphite of the forged needle coke secondary particles and inorganic carbon are mixed at a mass ratio of (3-4): (1-2) at a temperature of 80-90° C., so that the inorganic carbon is uniformly coated on the surface of the graphite, and then the coated graphite is cured, pyrolyzed and asphalt carbonized; A2, using chemical vapor deposition method, placing the product of step A1 in an ethylene atmosphere at a temperature of 150-200° C. for a reaction time of 1-2 hours; A3, placing the product of step A2 in a reactor, mixing the effective components of ethylene tar and catalytic oil slurry in a ratio of (1-2): (1-2) and adding them to the reactor, adding the catalyst and the cross-linking agent to the reactor, heating to 240-330° C., controlling the reaction pressure to 0.5-2.5 MPa, the stirring speed of the reactor to 150-450 r / min, and the reaction time to 3-4 h; A4. Slowly release the pressure to normal pressure, introduce air into the bottom of the reactor at an air intake rate of 0.5-2L / min, stir the reactor at a speed of 200-350r / min, set the reaction temperature at 240-300°C, and react for 2-6h. Stop introducing air and stirring, and then remove the light components to obtain the modified negative electrode material.
4. The low-temperature, high-power lithium-ion battery according to claim 3, characterized in that: The catalyst is p-toluenesulfonic acid, and its content is 3%-8% of the total mass of the raw materials; the cross-linking agent is one of trioxymethylene and polyoxymethylene, and its content is 7%-12% of the total mass of the raw materials.
5. The low temperature and high power lithium ion battery according to claim 2, characterized in that: The conductive agent is a mixture of superconducting carbon black and SWCNT single-walled carbon tubes, and the binder is PAA polyacrylonitrile multi-polymer emulsion.
6. The low temperature and high power lithium ion battery according to claim 1, characterized in that: The steps of preparing the positive electrode sheet include: S201, preparation of composite materials, electrochemically anodic boronizing a titanium sheet in an organic solution containing 0.5wt% NH4BF4, 5wt% deionized water and ethylene glycol as solvent, and then anodic oxidation in an organic solution containing fluoride ions, heat treating the oxidized sample in a resistance furnace at 200-450°C, keeping the temperature for 2h, and then cooling it to room temperature with the furnace; using the heat-treated boron-doped titanium oxide nanoarray as a matrix, vacuumizing and heating, and then sputtering a molybdenum disulfide target with a radio frequency power supply, cooling to 45°C and taking it out to obtain a composite material; S202, mixing the composite material and the positive electrode active material at a certain temperature, and then curing the positive electrode active material coated with the composite material to obtain a modified positive electrode material; S203, the modified positive electrode material, the conductive agent and the binder are mixed in a mass ratio of (96-98): (1-2): (1-2), and prepared into a slurry by a high-speed dispersing device. After coating, roller compaction and slitting, a positive electrode sheet of corresponding length is made, and a copper-plated composite nickel electrode ear is formed in the middle of the positive electrode sheet and glued.
7. The low-temperature, high-power lithium-ion battery according to claim 6, characterized in that: In step S202, the composite material and the positive electrode active material are mixed at a mass ratio of (3-4): (1-2) at a temperature of 80-90°C.
8. The low-temperature, high-power lithium-ion battery according to claim 7, characterized in that: The positive electrode active material is prepared by adding lithium cobalt oxide, ternary material and lithium manganese oxide into a stirring tank in a ratio of (1-2): (5-7): (2-3) and mixing.
9. The low temperature and high power lithium ion battery according to claim 1, characterized in that: The solvent components of the electrolyte include ethyl acetate, methyl propionate and methyl acetate; the lithium salt includes lithium bis(fluorosulfonyl)imide, and the additives include vinyl sulfate and triphosphite.
10. The low temperature and high power lithium ion battery according to claim 9, characterized in that: The mass ratio of ethyl acetate, methyl propionate and methyl acetate is (1-2):(1.5-2):(1-3); the mass ratio of vinyl sulfate and triphosphite is (1-2):(1-2).
Citation Information
Patent Citations
Lithium ion battery
CN104779413A
Preparation method of titanium dioxide nano-tube array immobilized spherical molybdenum disulfide negative electrode material for lithium battery
CN106684352A
Preparation method of bud-shaped molybdenum sulfide-titanium dioxide-B composite material as well as product and application thereof
CN114349054A
Positive plate and lithium ion battery
CN115066767A
Modification method for constructing MoS2 / NiO / TiO2 coated lithium manganese iron phosphate positive electrode material
CN118771334A
Cited By
Carbon-molybdenum disulfide composite negative electrode material and preparation method and application thereof
CN119943916A